LANGUAGE TRANSFER IN THE ACQUISITION OF IDIOMS IN A SECOND LANGUAGE : A STUDY OF FOURTH-YEAR FAST-TRACK STUDENTS AT FELTE, ULIS, VNU - Phạm, Thanh Mai (2021)
Vocabulary and grammar are two key factors in language. Within vocabulary, idioms play an important role in language learning. As communicative language teaching (CLT) approach with its aim to create “communicative competence” (Hymes, 1972) is becoming more popular, real life language like idioms draws more attention from educationalists. Furthermore, according to Gass (1979), the forms and patterns of the native language affect second language learning. Accordingly, the current research aimed at investigating the role of L1 on idiom acquisition of Vietnamese learners of English regarding their ability to comprehend and produce idioms. The target population of this study was fourth-year Fast-track students at the Faculty of English Language Teacher Education, Universities of Languages and International Studies, Vietnam National University. 9 students in group QH2008.1.E1were chosen randomly to do two tests: a recognition test and a recall test. The same set of 30 idioms was used in two tests, including: 10 identical, 10 similar and 10 different idioms. The findings of the study revealed that idioms were transferrable. Specifically, at recognition level, it appeared that subjects were able to generalize from the meaning in their first language to the meaning in the second language if the form was identical or similar. There was no evidence of language transfer in the case of different idioms. Regarding recall competence, positive transfer was likely to occur when students produced identical idioms. Producing similar idioms was as difficult as producing different idioms. Negative transfer was evident for similar idioms when students tended to use those in L1 to produce equivalent forms in L2. Little transfer would occur when students produced different idioms. The findings from the study hopefully would benefit not only researchers but teachers and readers who are interested in the same topic as well